2000
DOI: 10.1508/cytologia.65.141
|View full text |Cite
|
Sign up to set email alerts
|

Cytophotometric Estimation of 4C DNA Content and Chromosome Analysis in Four Species of Astrophytum Lem. of the Family Cactaceae.

Abstract: Karyotype analysis including determination of somatic chromosome number, chromosome length and volume, 4C DNA content and Interphase Chromosome Volume (INV) were carried

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
(7 reference statements)
3
6
0
2
Order By: Relevance
“…Regarding the satellites, there is variability among the few karyotypically studied cactus species: from one (Las Peñas et al, 2008, as here found for S. mirabilis, to 2-4 pairs (e.g., Cota and Philbrick 1994;Cota and Wallace 1995;Bandyopadhay and Sharma 2000;Das et al 1999Das et al , 2000Das and Mohanty 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Regarding the satellites, there is variability among the few karyotypically studied cactus species: from one (Las Peñas et al, 2008, as here found for S. mirabilis, to 2-4 pairs (e.g., Cota and Philbrick 1994;Cota and Wallace 1995;Bandyopadhay and Sharma 2000;Das et al 1999Das et al , 2000Das and Mohanty 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Pyrrhocactus species had small chromosomes, as it is the rule in Cactaceae (e.g. Cota and Philbrick 1994, Cota and Wallace 1995, Bandyopadhyay and Sharma 2000, Das et al 2000. Effectively, the largest chromosomes reached 4.5 lm (in Echinocereus: Cota and Wallace 1995) and the smallest ca.…”
Section: Discussionmentioning
confidence: 92%
“…Effectively, the largest chromosomes reached 4.5 lm (in Echinocereus: Cota and Wallace 1995) and the smallest ca. 1.5 lm (in Mammilaria, Echinopsis, and Opuntia, among other genera; Pinkava et al 1977, Bandyopadhyay and Sharma 2000, Das et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Na maioria dos estudos cariotípicos, quando não são todos os cromossomos metacêntricos, encontra-se apenas um ou dois submetacêntricos em todo o conjunto (BRIO-NES et al, 2004;DEL ANGEL et al, 2006;LAS PEÑAS et al, 2009), com exceção Schlumbergera, no qual foram encontrados 5 cromossomos submetacêntricos em duas espécies (ORTOLANI et al, 2007 Das et al (1998bDas et al ( , 2000 e Das e Mohanty (2006) utilizaram classificação dos cromossomos propondo-se quatro tipos. No tipo A os cromossomos apresentam tamanho médio e duas constrições; no tipo B, cromossomos possuem tamanho médio a pequeno, com uma constrição na posição sub-terminal e o satélite está localizado no braço longo do cromossomo; no tipo C os cromossomos têm tamanho de médio a pequeno, com constrições mediana; e, por fim, no tipo D os cromossomos são de tamanho médio a pequeno com constrições sub-medianas.…”
Section: Estudos Cariotípicosunclassified
“…São exemplos os estudos de Mohanty et al (1996), Mohanty et al (1997) e Das et al (1998b, que estudaram diversas espécies de Mammillaria (com variação de 9,1 pg em M. klissingiana Boed. a 26,46 pg em M. plumosa F.A.C.Weber), Das et al (2000), que estudaram quatro espécies de Astrophytum Lem. (que variaram de 9,23 pg a 10,12 pg), Das et al (1998aDas et al ( e 1998b …”
Section: Estudos Cariotípicosunclassified